The Persuasive Role of Meta-Discourse Markers in Digital Advertising - Ali, Sri Widyarti; Husain, Nurlaila (Universitas Nurul Jadid, 2023)
This study investigates the persuasive use of interactive and interactional meta-discourse markers in digital advertising, employing Hyland's (2005) model. Interactive meta-discourse encompasses transition markers, frame markers, endophoric markers, evidential, and code glosses, while interactional meta-discourse includes hedges, boosters, attitude markers, self-mentions, and engagement markers. The process of data collection includes extracting data from websites with digital advertisements, analyzing the use of meta-discourse markers in these ads to understand their context and purpose, and categorizing these markers into interactive and interactional categories. Data analysis involves identifying and examining the presence of these markers in digital advertising, interpreting how they contribute to persuasion in the text, and presenting the findings by categorizing interactive and interactional meta-discourse markers while explaining their persuasive significance. The research reveals that in advertisements for beauty products and luxury cars, transition markers are the sole category of interactive meta-discourse used. In contrast, interactional meta-discourse exhibits a broader range of categories in advertising, encompassing attitude markers, self-mention, engagement markers, and boosters.